Agricultural trade policies in the Andean Group : issues and options Tim Josling.. - Josling, Tim, 1940- (World Bank technical paper, 1997)
"Chapter on Ecuador offers a comparison with other Andean Pact countries. Argues that Ecuador is most in need of stability and security offered by regional market access"--Handbook of Latin American Studies, v. 57.